1898 Ga. L. 60, ch. 103 - (:unkn) unknown (General Publisher, 1898)
Prohibited the concealed carry of any pistol, dirk, sword cane, spear, Bowie knife, other kind of knife “manufactured and sold for purpose of offense and defense,” and any “kind of metal knucks.”
--
Keywords: CARRY - CONCEALED